The International Day of Light - May 16th - Dorosz, Dominik (Photonics Letters of Poland, 2017)
During 39th session of UNESCO General Conference which held on 7 November 2017 the date May 16th was proclaimed as International Day of Light (IDL). This decision was made after the success of the International Year of Light (IYL) celebrated in 2015. It confirmed that raising awareness of the social role of photonics is crucial for further development. Based on the rich experience of IYL 2015 ("more than 13,000 activities took place in 147 countries to reach an estimated 100 million people"), the most important goals are to be followed by the IDL, including: raising social awareness, education, showing the influence of photonics on culture and art, promoting foreign cooperation and the important role of conducting basic research. As a result, it will lead to the creation of new solutions based on photonic technology, which has resulted in increased energy efficiency and improved quality of our life.